Construction and evaluation of a universal influenza mRNA vaccine - TIAN Yuying; TIAN Yuying; DENG Zhuoya (陆军军医大学学报, 2024)
Objective To construct a universal influenza mRNA vaccine and evaluate its immunogenicity. Methods The antigen sequence of hemagglutinin (HA), nucleoprotein (NP) and matrix protein 2 ectodomain (M2e) in influenza A/California/04/2009 was optimized.HA, NP and 3 tandem M2e (3M2e) were cloned into pcDNA3.1 vector, respectively.Then the mRNAs were synthesized by linearization, in vitro transcription, enzymatic capping and enzymatic tailing, and named as mRNA-HA, mRNA-NP and mRNA-3M2e, respectively.The protein expression of the 3 kinds of mRNAs in 293T cells was detected by immunofluorescence assay.Comb-mRNA vaccine was prepared by enveloped mRNA-HA, mRNA-NP and mRNA-3M2e with lipid nanoparticles, respectively, and the particle size and potential were identified.Twenty-eight 6-week-old female BALB/c mice (18~22 g) were randomly divided into LNP group (n=14) and Comb-mRNA group (n=14).Hemagglutination inhibition (HI) method and microneutralization (MN) test were used to evaluate the serum antibody titer induced by Comb-mRNA vaccines.The mice were infected by 5LD50 wild-type H1N1 influenza virus to evaluate the protective efficacy. Results The mRNA-HA, mRNA-NP and mRNA-3M2e were successfully constructed, and the 3 mRNAs could be expressed in 293T cells.The average size of mRNA encapsulated by lipid nanoparticles was 119.53±6.5 nm, and the average potential was-8.23±1.3 mV.The geometric mean titer (GMT) of HI and MN in the Comb-mRNA group were 179.6 and 201.6, compared with the LNP group.The ratio of IFN-γ+CD4+/CD8+T cells was increased.The Comb-mRNA group could provide protection against 5LD50 wild type influenza H1N1 virus after 2 weeks of booster immunization. Conclusion Comb-mRNA, an influenza vaccine candidate, can induce immune responses and protect mice from influenza virus challenge.